Una misma exclamación del sultán Salah al-Din y del Miramolin al-Násir en las batallas de Hittin/Hattin (583 H./1.187 JC.) y al 'Iqab/LasNavas de Tolosa (6O9 H./1212 JC.). - Elhaj Soulami, Ben; Alvira Cabrer, Martín (Anaquel de Estudios Árabes, 2002)
Sin resumen